Design and fabrication of fiber mesh actuators. (December 2022) - Sauter, Tilman; Kratz, Karl; Farhan, Muhammad; Heuchel, Matthias; Lendlein, Andreas
Highlights: Performance of soft fiber mesh actuators can be tuned by spatial arrangement and chemical reinforcement of fibers. Design criteria are formation of fiber bundles, angle between fiber bundles in different stacked layers and covalent crosslinks forming within and between fibers. Anisotropic behavior and soft-tissue like elastic deformability can be realized. Soft robot skins or active patches supporting tissue regeneration are potential future applications. Abstract: Soft actuator performance can be tuned by chemistry or mechanical manipulation, but this adjustability is limited especially in view of their growing technological relevance. Inspired from textile engineering, we designed and fabricated fiber mesh actuators and introduced new features like anisotropic behavior and soft-tissue like elastic deformability. Design criteria for the meshes are the formation of fiber bundles, the angle between fiber bundles in different stacked layers and covalent crosslinks forming within and between fibers at their interfacial contact areas. Through crosslinking the interfiber bond strength increased from a bond transmitting neither axial nor rotational loads (pin joint) to a bond strength capable of both (welded joint). For non-linear elastic stiffening, stacked fiber bundles with four embracing fibers were created forming microstructural rhombus shapes. Loading the rhombus diagonally allowed generation of "soft tissue"-like mechanics. By adjustment of stacking angles, the point of strong increase in stress is tuned. While the highest stresses are observed in aligned and crosslinked fiber mats along the direction of the fiber, the strongest shape-memory actuation behavior is found in randomly oriented fiber mats. Fiber mesh actuators controlled by temperature are of high significance as soft robot skins and as for active patches supporting tissue regeneration. Graphical abstract: Image, graphical abstract